Underlying factors behind the low participation rate in electronic waste recycling - R. Siringo; H. Herdiansyah; R.D. Kusumastuti (Global Journal of Environmental Science and Management)
This study aims to understand influential factors for Jakarta’s residents to participate in a formal electronic waste recycling programme. It questions the efficacy of providing facilities to collect electronic waste despite the lack of legislated regulations or policies. Using the goal-framing theory as a foundation, a survey conducted on 208 respondents in 2018 revealed that selling obsolete electronic devices to peddlers or retaining them at home were standard practices in society, and only 2% of respondents recycled their electronic waste at formal facilities. The results show that electronic waste recycling intention correlates highest with information and convenience, 0.521 and 0.411, respectively. While knowledge has the least correlative value with attitude and intention, that is 0.204 and 0.240.  It clarifies that the normative goal is weaker than hedonic and gain goals. Respondents had enough awareness about the hazards of electronic waste. However, their behaviour did not exhibit it. It is imperative to lessen the gap between normative and hedonic goals by campaigning continuously and place the facilities at easily accessible locations to increase recycling participation. Furthermore, collecting electronic waste requires a collaboration between the government and electronics businesses, and must be supported by a legal framework.